Porokeratotic eccrine ostial and dermal duct nevus. - Rane, Meghana; Gole, Prachi; Khade, Pandharinath (European Journal of Pediatric Dermatology, 2024)
Porokeratotic eccrine ostial and dermal duct nevus (PEODDN) is a rare condition characterized by grouped, asymptomatic, linearly distributed keratotic papules and plaques on the extremities, with the characteristic histopathological appearance of porokeratosis. It is a disorder of keratinization involving the intraepidermal eccrine duct (acrosyringium) and is characterized histologically by eccrine hamartoma with cornoid lamella. Lesions usually present at birth or during childhood. We present a case of systematized PEODDN with scoliosis in an 8-year-old boy showing hyperkeratotic verrucous lesions on the palm, forearm, upper arm, legs and trunk along the lines of Blaschko, predominantly on the right side of the body since the age of 1 year with its characteristic dermoscopic and histopathological features.